The role of tumoral stroma in determining the forecast of recurrence and fatal consequence of stage IIA-IIIB colorectal cancer - Alina Yakimenko (Scientific Route OÜ, 2021)
Colorectal cancer (CRC) ranks 2nd in the structure of mortality from malignant neoplasms (MN). One of the criteria for the prognosis of CRC may be a tumor stroma, which has not been widely used in clinical practice.